Passivation process of perovskite layer and preparation process of perovskite solar cell
Through the two-step passivation process, the advantages of the first passivation agent and the second passivation agent are utilized to penetrate into the microstructure of the perovskite film and increase the dipole moment respectively, which solves the problem of insufficient passivation efficiency and stability of the surface and interface defects of the perovskite solar cell module, and achieves efficient passivation and long-term stability of the module.
Patent Information
- Application Number
- CN202411849688.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-04
AI Technical Summary
In the prior art, the passivation efficiency and stability of the surface and interface defects of perovskite solar cell modules are insufficient, which limits the efficiency and long-term stability of the module.
The two-step passivation process is adopted. First, the perovskite surface is initially treated with the first passivation agent, and the surface defects are penetrated into the microstructure of the film with its small volume advantage; second, the second passivation agent is used for further treatment, and the dipole moment is increased by its larger volume and structure, the energy level arrangement is improved, and the water-oxygen barrier property is stronger.
The photoelectric conversion efficiency and long-term stability of perovskite solar cell modules have been significantly improved, and the overall performance of the module is improved by optimizing the photoelectric characteristics of perovskite films and enhancing environmental stability.
Smart Images

Figure CN119767994A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solar cells, and in particular to a passivation process for a perovskite layer and a preparation process for a perovskite solar cell. Background Art
[0002] Perovskite solar cells have become the focus of research due to their excellent optoelectronic properties. However, the efficiency and stability of large-area perovskite modules are the main obstacles to their commercialization. This is mainly because there are a large number of defects on the surface and interface of large-area perovskite films. These defects not only capture photogenerated carriers as non-radiative recombination centers, reducing the efficiency of the module, but also serve as ion migration channels and water and oxygen corrosion paths, further reducing the stability of the module. Therefore, effective passivation of surface and interface defects of large-area perovskite modules is crucial to improving their efficiency and stability.
[0003] At present, the main methods for defect passivation of perovskite components include:
[0004] 1. Spin coating: Due to the uneven distribution of centrifugal and centripetal forces during the spin coating process, and more than 95% of the passivation agent is wasted during the spin coating process, this method is not suitable for the application of large-area components.
[0005] 2. Liquid immersion method: The entire component coated with the perovskite layer is immersed in the passivating agent, and taken out after sufficient reaction to achieve the passivation effect. This method has low production efficiency and serious waste of passivating agent, which does not meet the requirements of efficiency and environmental protection.
[0006] 3. Direct coating method: Due to the rapid evaporation rate of the solvent, the passivation is uneven, with excessive accumulation at the front end and insufficient accumulation at the end.
[0007] 4. Gas phase passivation method: By heating, the passivator molecules are volatilized to the surface of the perovskite, interacting with the defects to achieve passivation. This method can efficiently and uniformly process large-area components.
[0008] Although the vapor phase passivation method has advantages in passivating large-area perovskite components, the existing one-step vapor phase passivation method still has room for improvement in efficiency and stability. The existing vapor phase passivation method is not ideal, and the limitations of the one-step passivation method are obvious, which requires further research and improvement. Therefore, the development of a simple and efficient interface defect passivation technology is of great significance to further improve the performance of perovskite components.
[0009] In view of this, the present invention is proposed. Summary of the invention
[0010] One of the objectives of the present invention is to provide a passivation process for a perovskite layer to solve at least one of the above-mentioned technical problems in the prior art.
[0011] A second object of the present invention is to provide a process for preparing a perovskite solar cell.
[0012] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0013] The first aspect of the present invention provides a passivation process for a perovskite layer, wherein a first passivation is performed on the perovskite layer of a conductive substrate using a first passivator solution, and then a second passivation is performed using a second passivator solution to obtain a passivation layer;
[0014] Wherein, the number of C atoms of the first passivating agent is less than 5;
[0015] The number of C atoms in the second passivator is ≥5.
[0016] Furthermore, the passivator is a first passivator and / or a second passivator.
[0017] Preferably, the passivator includes at least one of a quaternary ammonium salt passivator, a phosphoric acid passivator, an organic amine passivator, a carboxylic acid passivator and a sulfonic acid passivator.
[0018] Furthermore, the concentration of the passivating agent solution is 1 to 100 g / L, preferably 40 to 60 g / L.
[0019] Preferably, the conductive substrate containing the perovskite layer is inverted on the passivator solution so that the perovskite layer faces the passivator solution, and the passivator solution is heated or evacuated to volatilize the passivator and passivate to form a passivation layer.
[0020] Preferably, the heating temperature is 40-80° C. and the heating time is 3-8 min.
[0021] Preferably, the vacuum degree of the vacuum extraction is 1-1000 Pa.
[0022] A second aspect of the present invention provides a process for preparing a perovskite solar cell, comprising the passivation process.
[0023] Furthermore, the preparation process of the perovskite solar cell is: preparing a hole transport layer, a perovskite layer, a passivation layer, an electron transport layer, a hole blocking layer and depositing a metal electrode in sequence on a pretreated conductive substrate to obtain the perovskite solar cell.
[0024] The passivation layer is prepared by adopting the passivation process.
[0025] Furthermore, the pretreatment process includes performing P1 scribing, cleaning, drying and activation processes on the conductive substrate.
[0026] Preferably, the conductive substrate comprises ITO glass or FTO glass, preferably ITO glass.
[0027] Preferably, the laser frequency of the P1 scribing is 50-500 kHz, and the laser energy is 20-100 μJ.
[0028] Preferably, the width of the P1 scribing line is 80-300 μm, and the speed is 100-300 mm / s.
[0029] Preferably, the cleaning reagents include a cleaning solution specifically for conductive glass, deionized water and an organic solvent used in this order.
[0030] Preferably, the organic solvent comprises isopropyl ketone and / or acetone.
[0031] Preferably, the cleaning time of each cleaning reagent is 15 to 25 minutes.
[0032] Preferably, the drying method includes drying by oven or drying by air gun.
[0033] Preferably, the drying temperature is 60-80° C. and the drying time is 18-36 hours.
[0034] Preferably, the activation method includes activation by ultraviolet ozone machine or cleaning activation by plasma cleaning machine.
[0035] Preferably, the activation time is 5 to 20 minutes.
[0036] Furthermore, the preparation method of the hole transport layer is:
[0037] The hole transport layer solution is coated on the pretreated conductive substrate by slit coating, spin coating, magnetron sputtering, scraping, inkjet printing or atomic layer deposition, and then annealed to obtain the hole transport layer.
[0038] Preferably, the hole transport layer is made of Me-4PACz, PTAA, PETDOS:PSS, CuPc, poly-TPD, 2PACz, MeO-4PADBC or nickel oxide.
[0039] Preferably, the solvent in the hole transport layer solution includes ethanol, 2-ME or DMF.
[0040] Preferably, the annealing temperature is 80-120° C. and the annealing time is 8-12 min.
[0041] Furthermore, the preparation method of the perovskite layer is:
[0042] The perovskite precursor solution is coated on the hole transport layer by slit coating, vacuum evaporation, magnetron sputtering, inkjet printing or doctor blade coating, and then high and low temperature annealing is performed to obtain the perovskite layer.
[0043] Preferably, the high and low temperature annealing method is to first perform low temperature annealing and then perform high temperature annealing.
[0044] Preferably, the low-temperature annealing is performed at a temperature of 60 to 80° C. and for a time of 30 to 90 seconds.
[0045] Preferably, the high temperature annealing is performed at a temperature of 110 to 130° C. and for a time of 8 to 12 minutes.
[0046] Preferably, the perovskite precursor solution comprises at least one of methylamine hydroiodide, formamidine hydroiodide, rubidium iodide, lead iodide and lead bromide.
[0047] Preferably, the solvent in the perovskite precursor solution includes at least one of DMF, NMP, 2-Me, DMSO and DMPU.
[0048] Furthermore, the preparation method of the electron transport layer is:
[0049] The electron transport layer material is deposited on the passivation layer by vacuum evaporation or magnetron sputtering to obtain the electron transport layer.
[0050] Preferably, the thickness of the electron transport layer is 20-60 nm.
[0051] Preferably, the electron transport layer material includes C60, PCBM or titanium dioxide.
[0052] Furthermore, the preparation method of the hole blocking layer is:
[0053] The hole blocking layer material is deposited on the electron transport layer by vacuum evaporation or atomic layer deposition to obtain the hole blocking layer.
[0054] Preferably, the hole blocking layer has a thickness of 6-7 nm.
[0055] Preferably, the hole blocking layer material includes BCP or tin dioxide.
[0056] Furthermore, it also includes P2 scribing after preparing the hole blocking layer and before depositing the metal electrode.
[0057] Preferably, the laser frequency of the P2 scribing is 50-500 kHz, and the laser energy is 20-100 μJ.
[0058] Preferably, the width of the P2 scribing line is 40-300 μm, and the speed is 50-500 mm / s.
[0059] Preferably, the electrode material is deposited by vacuum evaporation to obtain the metal electrode.
[0060] Preferably, the thickness of the metal electrode is 50-200 nm.
[0061] Preferably, the electrode material includes copper, silver or gold.
[0062] Compared with the prior art, the present invention has at least the following beneficial effects:
[0063] The passivation process provided by the present invention adopts a two-step passivation process to achieve efficient passivation of surface defects of perovskite solar cell modules, so as to significantly improve the photoelectric conversion efficiency and long-term stability of the modules. In this process, the first passivator is first used to preliminarily treat the surface of the perovskite, and its small volume advantage is used to more easily penetrate into the microstructure of the perovskite film, fully contact and passivate those surface defects that are usually non-radiative recombination active centers, which will capture photogenerated carriers and reduce battery efficiency. The preliminary passivation of the first passivator effectively reduces these non-radiative recombination centers, improves the collection efficiency of photogenerated carriers, and thus improves the overall performance of the module. Then, the second step of the present invention is to apply the second passivator for further treatment. The second passivator can increase the dipole moment and improve the energy level arrangement due to its larger volume and structure, making it more reasonable, which is crucial for the carrier transmission and collection of perovskite solar cells, because it can reduce energy loss and improve the open circuit voltage and fill factor of the battery. At the same time, due to the characteristics of its molecular structure, the second passivator has a stronger water and oxygen barrier, which can effectively prevent moisture and oxygen from penetrating the perovskite layer, protect the internal structure of the battery from corrosion, and extend the service life of the battery. The passivation process of the present invention optimizes the photoelectric properties of the perovskite film at the microscopic level and enhances the environmental stability of the component at the macroscopic level through the synergistic effect of the two-step method. This comprehensive passivation strategy can effectively improve the efficiency and long-term stability of large-area perovskite solar cell components.
[0064] The preparation process provided by the present invention, in view of the advantages brought by the above-mentioned passivation process, enables the perovskite solar cell to have higher efficiency and stability. The preparation process provided by the present invention, through fine control and optimized design, not only improves the photoelectric conversion efficiency of the battery, but also enhances the stability and durability of the battery in practical applications. The perovskite solar cell obtained by this preparation process can show good long-term stability while maintaining high efficiency, which is of great significance for promoting the commercialization and large-scale application of perovskite solar cell technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0065] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0066] Figure 1 A schematic diagram of the passivation process provided by the present invention;
[0067] Figure 2 This is the fluorescence spectrum obtained in Test Example 1;
[0068] Figure 3 This is the IV curve obtained in Test Example 2. DETAILED DESCRIPTION
[0069] The embodiments of the present invention will be described in detail below in conjunction with the embodiments and examples, but those skilled in the art will understand that the following embodiments and examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0070] The "perovskite solar cell" or "perovskite cell" mentioned below in the present invention includes but is not limited to formal perovskite cells, formal perovskite modules, inverted perovskite cells, inverted perovskite modules, small-area perovskite cells, small-area perovskite modules, single-junction perovskite cells, single-junction perovskite modules, perovskite-organic stacked cells, perovskite-organic stacked modules, perovskite-perovskite stacked cells, perovskite-perovskite stacked modules, perovskite-crystalline silicon stacked cells, perovskite-crystalline silicon stacked modules, perovskite-copper indium gallium tin stacked cells, and perovskite-copper indium gallium tin stacked modules.
[0071] The first aspect of the present invention provides a passivation process for a perovskite layer, wherein a first passivation is performed on the perovskite layer of a conductive substrate using a first passivator solution, and then a second passivation is performed using a second passivator solution to obtain a passivation layer;
[0072] Wherein, the number of atoms of C in the first passivating agent is less than 5;
[0073] The number of C atoms in the second passivator is ≥5.
[0074] The passivation process provided by the present invention adopts a two-step passivation process, aiming to combine the advantages of the first passivator and the second passivator to achieve efficient passivation of the surface defects of the perovskite solar cell module, so as to significantly improve the photoelectric conversion efficiency and long-term stability of the module. In this process, the first passivator is first used to preliminarily treat the surface of the perovskite, and its small volume advantage is used to more easily penetrate into the microstructure of the perovskite film, fully contact and passivate those surface defects that are usually used as non-radiative recombination active centers, which will capture photogenerated carriers and reduce battery efficiency. The preliminary passivation of the first passivator effectively reduces these non-radiative recombination centers, improves the collection efficiency of photogenerated carriers, and thus improves the overall performance of the module. Then, the second step of the present invention is to apply the second passivator for further treatment. The second passivator can increase the dipole moment and improve the energy level arrangement due to its larger volume and structure, making it more reasonable, which is crucial for the carrier transport and collection of perovskite solar cells, because it can reduce energy loss and improve the open circuit voltage and fill factor of the battery. At the same time, due to the characteristics of its molecular structure, the second passivator has a stronger water and oxygen barrier, which can effectively prevent moisture and oxygen from penetrating the perovskite layer, protect the internal structure of the battery from corrosion, and extend the service life of the battery. The passivation process of the present invention optimizes the photoelectric properties of the perovskite film at the microscopic level and enhances the environmental stability of the component at the macroscopic level through the synergistic effect of the two-step method. This comprehensive passivation strategy can effectively improve the efficiency and long-term stability of large-area perovskite solar cell components.
[0075] Specifically, the passivation process provided by the present invention is a two-step passivation technology, which aims to achieve efficient passivation of surface defects of perovskite solar cell modules by combining the advantages of the first passivator and the second passivator, thereby significantly improving the photoelectric conversion efficiency and long-term stability of the modules. Figure 1 As shown in the figure, the first step of the process is to use the first passivator to preliminarily treat the perovskite surface. Due to its small size, the first passivator can more easily penetrate into the microstructure of the perovskite film, fully contact and passivate surface defects, which are usually active centers of non-radiative recombination, capture photogenerated carriers and reduce battery efficiency. Through the preliminary passivation of the first passivator, these non-radiative recombination centers can be effectively reduced, the collection efficiency of photogenerated carriers can be improved, and the overall performance of the component can be improved.
[0076] On the basis of the first passivator, the second step of the present invention is to apply the second passivator for further treatment. Due to its larger volume and structure, the second passivator can increase the dipole moment, which helps to improve the energy level arrangement of the second passivator and make it more reasonable. Reasonable energy level arrangement is crucial for carrier transport and collection of perovskite solar cells because it can reduce energy loss and improve the open circuit voltage and fill factor of the battery. In addition, due to the characteristics of its molecular structure, the second passivator has a stronger water-oxygen barrier, which can effectively prevent moisture and oxygen from penetrating the perovskite layer, thereby protecting the internal structure of the battery from erosion and extending the service life of the battery.
[0077] The passivation process of the present invention not only optimizes the photoelectric properties of the perovskite film at the microscopic level, but also enhances the environmental stability of the component at the macroscopic level through the synergistic effect of the two-step method. This comprehensive passivation strategy can effectively improve the efficiency and long-term stability of large-area perovskite solar cell components, providing important technical support for the commercialization and large-scale application of perovskite solar cells. Through the application of this passivation process, it can be expected that perovskite solar cells will show higher performance and longer service life in practical applications, further promoting the development of renewable energy technology.
[0078] In the passivation process of perovskite solar cells, only the first passivator is used for the first step of treatment. Although it can effectively penetrate into the microstructure of the perovskite film, passivate surface defects, and improve the collection efficiency of photogenerated carriers, due to the small size of the first passivator, they cannot form a sufficiently strong dipole moment on the surface of the perovskite film, which will lead to unreasonable energy level arrangement, thereby affecting the transmission efficiency of electrons and holes and reducing the performance of the battery. At the same time, the first passivator has relatively weak barrier capacity for water and oxygen, and cannot effectively protect the perovskite layer from erosion by environmental factors, thus affecting the long-term stability of the battery.
[0079] On the contrary, if only the second passivator treatment in the second step is used, although it can increase the dipole moment, improve the energy level arrangement, and enhance the water and oxygen barrier, due to the large volume of the second passivator, they may not be able to fully penetrate into the microstructure of the perovskite film, resulting in insufficient passivation and failure to effectively cover all surface defects, thereby failing to completely suppress non-radiative recombination and affecting the photoelectric conversion efficiency of the battery.
[0080] When the first passivator and the second passivator are used at the same time, although the advantages of the two can be combined in theory, in fact, the passivation effect may be affected due to their interaction and competition on the surface of the perovskite film. The first passivator and the second passivator may interfere with each other, affecting each other's distribution and coverage on the surface of the perovskite, thereby reducing the passivation effect and failing to achieve the desired photoelectric performance and stability. Therefore, the two-step passivation technology proposed in the present invention avoids the above problems by precisely controlling the order and conditions of use of the passivators. This step-by-step passivation strategy not only ensures the maximization of the passivation effect, but also avoids the competitive influence between different passivators, and achieves a significant improvement in the photoelectric conversion efficiency and long-term stability of the perovskite solar cell module. Through this finely regulated passivation process, the advantages of the first passivator and the second passivator can be effectively balanced, and efficient passivation of surface defects of the perovskite solar cell module can be achieved, providing important technical support for the commercialization and large-scale application of perovskite solar cells.
[0081] Furthermore, the passivator is a first passivator and / or a second passivator.
[0082] Preferably, the passivator includes at least one of a quaternary ammonium salt passivator, a phosphoric acid passivator, an organic amine passivator, a carboxylic acid passivator and a sulfonic acid passivator.
[0083] Typical but non-limiting examples of quaternary ammonium salt passivating agents include but are not limited to ethylenediamine hydroiodide (EDADI), 4-trifluoromethylphenethylamine iodide (4-CF3-PEAI), cycloheximide-N-nitrobenzoate, phenethylammonium iodide, ethylenediamine iodide, propylenediamine iodide or butylenediamine iodide.
[0084] Typical, but not limiting, phosphoric acid-based passivating agents are typically, but not limited to, superphosphate and antimony triphosphate.
[0085] Typical but not limiting, organic amine passivating agents are typically but not limited to ethylenediamine (EDA), 4-trifluoromethylphenethylamine (4-CF3-PEA), phenethylamine iodide, ethylamine, propylenediamine, and butylenediamine.
[0086] Typical but not limiting examples of sulfonic acid passivating agents include, but are not limited to, 6-bromo-2-naphthyl trifluoromethanesulfonate (BNT), sodium 4-chlorobenzenesulfonate (4Cl-BZS), and 3-(decyldimethylamino)-propanesulfonate (DPSI).
[0087] Among the above passivators, the first passivator is typically but not limited to ethylenediamine hydroiodide (EDADI), propylenediamine hydroiodide (PDADI), and butylenediamine hydroiodide (BDADI).
[0088] The second passivating agent is typically, but not limited to, 4-trifluoromethylphenethylamine iodide (4-CF3-PEAI) and 3,5-bistrifluoromethylphenethylamine iodide (3,5-DCF3-PEAI).
[0089] Furthermore, the concentration of the passivating agent solution is 1 to 100 g / L, preferably 40 to 60 g / L.
[0090] Typically but non-limitingly, the concentration of the passivator solution can be 1g / L, 10g / L, 20g / L, 30g / L, 40g / L, 50g / L, 60g / L, 70g / L, 80g / L, 90g / L or 100g / L, or any value within the range of 1g / L to 100g / L; a preferred concentration range, for example, can be 40g / L, 45g / L, 50g / L, 55g / L, 59g / L or 60g / L, or any value within the range of 40g / L to 60g / L.
[0091] Preferably, the conductive substrate containing the perovskite layer is inverted on the passivator solution so that the perovskite layer faces the passivator solution, and the passivator solution is heated or evacuated to volatilize the passivator and passivate to form a passivation layer.
[0092] It should be noted that the "passivator solution" mentioned in the present invention refers to the first passivator solution and / or the second passivator solution; the "passivator" mentioned refers to the first passivator and / or the second passivator; and the "passivation" mentioned refers to the first passivation and / or the second passivation.
[0093] It should be noted that the “passivation layer” is formed through the first passivation and the second passivation.
[0094] The gas phase passivation method provided by the present invention causes less damage to the film. Since the interaction between the gas phase molecules and the perovskite layer is mainly achieved through volatilization and adsorption processes, this non-contact treatment method avoids the damage that may be caused by physical friction or chemical corrosion, thereby ensuring the integrity and structural stability of the perovskite layer. This mild treatment method allows the passivation process to be carried out without destroying the perovskite material, so that the passivator has sufficient time to be evenly distributed on the surface of the perovskite layer, fully contact and act with the surface defects, and achieve in-depth and effective passivation.
[0095] In this gas phase passivation process, the volatilization and adsorption of the passivator molecules is a dynamic equilibrium process, which allows the passivator to continue to exist on the surface of the perovskite film until it reaches saturation. This continuous passivation can not only cover newly formed surface defects, but also repair existing defects, ensuring the durability and stability of the passivation effect. Since the gas phase molecules cause minimal damage to the perovskite layer, this passivation method can achieve long-term and sufficient passivation without sacrificing the quality of the perovskite layer, thereby achieving the expected effect of improving the photoelectric conversion efficiency and enhancing the stability of the component.
[0096] In addition, the mildness of the gas phase passivation method also means that it can be carried out at a lower temperature, which helps to maintain the crystal structure and chemical stability of the perovskite layer and avoid material degradation or phase change that may be caused by high temperature treatment. Therefore, the gas phase passivation used in the present invention is not only an effective passivation method, but also a perovskite layer-friendly processing technology. It can achieve efficient, uniform and lasting passivation effects without damaging the perovskite film, providing strong support for the performance optimization and long-term stability of perovskite solar cells.
[0097] Preferably, the heating temperature is 40-80° C. and the heating time is 3-8 min.
[0098] Typically but not limitatively, the heating temperature can be 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C or 80°C, or any value within the range of 40°C to 80°C; the heating time can be 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min or 10 min, or any value within the range of 3 min to 10 min.
[0099] Preferably, the vacuum degree of the vacuum extraction is 1-1000 Pa.
[0100] Typically but not limitatively, the vacuum degree of the evacuation may be 1Pa, 100Pa, 200Pa, 300Pa, 400Pa, 500Pa, 600Pa, 700Pa, 800Pa, 900Pa or 100Pa, or any value within the range of 1Pa to 1000Pa.
[0101] A second aspect of the present invention provides a process for preparing a perovskite solar cell, comprising the passivation process.
[0102] The preparation process provided by the present invention, in view of the advantages brought by the above-mentioned passivation process, enables the perovskite solar cell to have higher efficiency and stability. The preparation process provided by the present invention, through fine control and optimized design, not only improves the photoelectric conversion efficiency of the battery, but also enhances the stability and durability of the battery in practical applications. The perovskite solar cell obtained by this preparation process can show good long-term stability while maintaining high efficiency, which is of great significance for promoting the commercialization and large-scale application of perovskite solar cell technology.
[0103] Furthermore, the preparation process of the perovskite solar cell is: preparing a hole transport layer, a perovskite layer, a passivation layer, an electron transport layer, a hole blocking layer and depositing a metal electrode in sequence on a pretreated conductive substrate to obtain the perovskite solar cell.
[0104] The passivation layer is prepared by adopting the passivation process.
[0105] Furthermore, the pretreatment process includes performing P1 scribing, cleaning, drying and activation processes on the conductive substrate.
[0106] Preferably, the conductive substrate comprises ITO glass or FTO glass, preferably ITO glass.
[0107] ITO stands for Indium-Tin-Oxide, while FTO stands for Fluorine-doped Tin Oxide. ITO glass or FTO glass are both transparent conductive glasses, used as the base material of solar cells.
[0108] P1 scribing is a laser scribing process performed on a conductive substrate. The purpose of this step is to form independent conductive oxide substrates and serve as positioning points for subsequent P2 and P3 scribing.
[0109] Preferably, the laser frequency of the P1 scribing is 50-500 kHz, and the laser energy is 20-100 μJ.
[0110] Preferably, the width of the P1 scribing line is 80-300 μm, and the speed is 100-300 mm / s.
[0111] Typically but not limiting, the laser frequency of the P1 marking can be 50kHz, 75kHz, 100kHz, 250kHz, 350kHz, 425kHz or 500kHz, or any value in the range of 50kHz to 500kHz; the laser energy can be 20μJ, 30μJ, 40μJ, 60μJ, 80μJ, 90μJ or 100μJ, or any value in the range of 20μJ to 100μJ. In addition, the width of the P1 line can be 80μm, 100μm, 120μm, 160μm, 200μm, 240μm or 300μm, or any value in the range of 80μm to 300μm; the marking rate can be 100mm / s, 150mm / s, 200mm / s, 250mm / s, 275mm / s or 300mm / s, or any value in the range of 100mm / s to 300mm / s.
[0112] Preferably, the cleaning reagents include a conductive glass cleaning liquid, deionized water and an organic solvent used in sequence to remove impurities and residual organic matter on the conductive substrate. During the cleaning process, the conductive substrate is completely immersed in the liquid and fully in contact with the liquid, thereby achieving a comprehensive cleaning effect.
[0113] Preferably, the organic solvent comprises isopropyl ketone and / or acetone.
[0114] Preferably, the cleaning time of each cleaning reagent is 15 to 25 minutes.
[0115] Typically but not limiting, the cleaning time of each cleaning agent can be 15 min, 16 min, 17 min, 18 min, 19 min, 20 min, 21 min, 22 min, 23 min, 24 min or 25 min, or any value within the range of 15 min to 25 min.
[0116] Preferably, the drying method includes drying by oven or air gun to remove the organic solvent remaining on the surface.
[0117] Preferably, the drying temperature is 60-80° C. and the drying time is 18-36 hours.
[0118] Typically but not limitatively, the drying temperature can be 60°C, 65°C, 70°C, 75°C, 80°C, and the time can be 18h, 20h, 24h, 28h, 30h, 32h, 34h or 36h, or any value within the range of 60°C to 80°C and 18h to 36h.
[0119] Preferably, the activation method includes activation by ultraviolet ozone machine or cleaning activation by plasma cleaning machine to improve the wettability of the conductive substrate.
[0120] Preferably, the activation time is 5 to 20 minutes.
[0121] Typically but not limiting, the activation time may be 5 min, 7 min, 10 min, 15 min, 18 min or 20 min, or any value within the range of 5 min to 20 min.
[0122] Furthermore, the preparation method of the hole transport layer is:
[0123] The hole transport layer solution is coated on the pretreated conductive substrate by slit coating, spin coating, magnetron sputtering, scraping, inkjet printing or atomic layer deposition, and then annealed to obtain the hole transport layer.
[0124] During the slit coating process, the hole transport layer is coated in an air atmosphere with a relative humidity of 10-50%. The liquid inlet pipe of the slit coater is first cleaned with a blank solvent, and then 15-30 mL of the prepared hole transport layer solution is added. The conductive substrate to be coated is placed in the slit coater, adsorbed and fixed on the base, and the surface dust is removed by air blowing. A series of parameters such as the length, width and thickness of the conductive substrate, the movement speed of the plunger pump and the platform, and the distance between the die head and the platform are set. The coating is started, and the die head moves relatively from one end of the substrate to the other end at a uniform speed in a straight line (some equipment moves the die head, and some equipment moves the base), and a uniformly wet film is coated on the substrate.
[0125] Taking magnetron sputtering of nickel oxide as an example, the conductive substrate is transferred to the magnetron sputtering system to deposit the nickel oxide film. A small flow of oxygen can be introduced during the sputtering process to improve the composition of the nickel oxide film. The substrate can be moderately heated during the whole process. The thickness of the nickel oxide is monitored by the crystal oscillator and the film thickness meter. When the thickness meets the requirements, the sputtering is stopped.
[0126] Preferably, the hole transport layer is made of Me-4PACz, PTAA, PETDOS:PSS, CuPc, poly-TPD, 2PACz, MeO-4PADBC or nickel oxide.
[0127] Preferably, the solvent in the hole transport layer solution includes ethanol, 2-ME or DMF.
[0128] Preferably, the annealing temperature is 80 to 120°C and the time is 8 to 12 minutes. The annealing process after the hole transport layer is coated is crucial. It not only helps to remove residual solvents, stabilize the crystal structure, and improve electron mobility, but also eliminates impurities and improves crystal quality, thereby improving the photoelectric efficiency of the battery. In addition, annealing further optimizes the photoelectric conversion efficiency and improves the stability and durability of the battery by adjusting the crystallinity and crystal morphology. At the same time, annealing can also improve the surface morphology of the hole transport layer, making it smoother and more uniform, thereby improving contact with the metal electrode, reducing resistance, and facilitating the transmission and collection of electrons. These combined effects significantly improve the performance of perovskite solar cells while ensuring the long-term stability and reliability of the battery.
[0129] Typically but not limiting, the annealing temperature may be 80°C, 90°C, 100°C, 110°C or 120°C, and the annealing time may be 8 min, 9 min, 10 min, 11 min or 12 min, or any value within the range of 80°C to 120°C and 8 min to 12 min.
[0130] Furthermore, the preparation method of the perovskite layer is:
[0131] The perovskite precursor solution is coated on the hole transport layer by slit coating, vacuum evaporation, magnetron sputtering, inkjet printing or doctor blade coating, and then high and low temperature annealing is performed to obtain the perovskite layer.
[0132] The perovskite layer is prepared by the slit coating method. The perovskite layer is coated in an air atmosphere with a relative humidity of 10-50%. The plunger pump, die head and liquid inlet pipeline are first cleaned with DMF solvent, and then the conductive substrate to be coated is placed on the slit coater. The dust on the glass surface is removed by air blowing, and it is adsorbed and fixed on the coating base. A series of parameters such as the length, width and thickness of the substrate, the movement speed of the plunger pump and the platform, and the distance between the die head and the platform are set. The coating is started, and the die head moves relatively from one end of the substrate to the other end at a uniform speed in a straight line, and a uniform wet film is coated on the substrate. In addition, the deposition method of the perovskite film can also be selected from vacuum evaporation, magnetron sputtering, inkjet printing, scraping and other suitable deposition methods.
[0133] Preferably, the high and low temperature annealing method is to first perform low temperature annealing and then perform high temperature annealing.
[0134] Preferably, the temperature of the low temperature annealing is 60-80°C and the time is 30-90s. The preliminary annealing at a relatively low temperature helps to remove the solvent while avoiding too fast a crystallization process. This helps to form a uniform perovskite precursor film, laying the foundation for the next step of high temperature annealing.
[0135] Typically but not limiting, the low temperature annealing temperature may be 60°C, 65°C, 70°C or 80°C, and the time may be 30s, 45s, 60s, 75s or 90s, or any value within the range of 60-80°C and 30s to 90s.
[0136] Preferably, the temperature of the high temperature annealing is 110-130°C and the time is 8-12 minutes. High temperature annealing at a higher temperature helps to promote the crystallization of the perovskite precursor and form uniform and high-quality perovskite crystals. This step is crucial to obtain high-efficiency perovskite solar cells, because uniform perovskite crystals can reduce defects and improve light absorption efficiency, thereby improving the overall performance of the cell.
[0137] Typically but not limiting, the high temperature annealing temperature can be 110°C, 115°C, 120°C, 125°C or 130°C, and the time can be 8 min, 9 min, 10 min, 11 min or 12 min, or any value within the range of 110°C to 130°C and 8 min to 12 min.
[0138] Through this two-step annealing process, the crystallization kinetics of the perovskite layer can be effectively controlled to ensure the uniform growth of the perovskite crystals, which is of great significance for improving the photoelectric conversion efficiency and stability of perovskite solar cells. In addition, this annealing strategy also helps to reduce non-radiative recombination during the battery manufacturing process, improve the open circuit voltage and fill factor of the battery, and further improve the performance of the battery.
[0139] Preferably, the perovskite precursor solution comprises at least one of methylamine hydroiodide, formamidine hydroiodide, rubidium iodide, lead iodide and lead bromide.
[0140] It should be noted that the present invention does not limit the composition of the perovskite precursor material, and any material that can form a perovskite layer can be used. The selected perovskite component can be at least one of methylamine hydroiodide, formamidine hydroiodide, rubidium iodide, lead iodide and lead bromide, or it can be replaced or added with other suitable materials such as methylamine hydroiodide, formamidine hydroiodide, rubidium iodide, lead iodide and lead bromide, and their various permutations and combinations of different materials, and the molar ratio of various components can be appropriately adjusted. The solvent of the selected perovskite precursor solution can also replace or add other suitable reagents such as 2-Me, DMSO, DMPU and their permutations and combinations, and the volume ratio of various reagents can be adjusted to obtain a perovskite light absorption layer with different band gaps and different performances.
[0141] Preferably, the solvent in the perovskite precursor solution includes at least one of DMF, NMP, 2-Me, DMSO and DMPU.
[0142] Furthermore, the preparation method of the electron transport layer is:
[0143] The electron transport layer material is deposited on the passivation layer by vacuum evaporation or magnetron sputtering to obtain the electron transport layer.
[0144] Preferably, the thickness of the electron transport layer is 20-60 nm. The deposition rate of the electron transport layer can be controlled between 0.005-0.02 nm / s, and the deposition thickness can be selected to be a suitable thickness between 20-60 nm.
[0145] Typically but not limiting, the thickness of the electron transport layer may be 20 nm, 30 nm, 40 nm, 50 nm or 60 nm, or any value within the range of 20 nm to 60 nm.
[0146] Preferably, the electron transport layer material comprises C60, PCBM or titanium dioxide. PCBM is [6.6]-phenyl-C 61 -Methyl butyrate.
[0147] Furthermore, the preparation method of the hole blocking layer is:
[0148] The hole blocking layer material is deposited on the electron transport layer by vacuum evaporation or atomic layer deposition to obtain the hole blocking layer.
[0149] Preferably, the thickness of the hole blocking layer is 6-7 nm. The hole blocking layer deposition rate can be selected from a range of 0.001-0.003 nm / s, and the deposition thickness can be selected from a range of 6-7 nm.
[0150] Preferably, the hole blocking layer material includes BCP or tin dioxide.
[0151] PCBM and BCP can be deposited by vacuum thermal evaporation (the vacuum degree of the equipment is 10 -4 to 10 -5 Titanium dioxide can be deposited by magnetron sputtering (the vacuum degree of the equipment is 10 -4 to 10 -5 Pa), tin dioxide can be deposited by atomic layer deposition (ALD).
[0152] Furthermore, it also includes P2 scribing after the hole blocking layer is prepared and before the metal electrode is deposited. The purpose of P2 scribing is to etch the hole transport layer, perovskite layer, passivation layer, electron transport layer, and hole blocking layer, exposing the conductive layer on the conductive substrate, so that the metal electrode deposited in the next step is in direct contact with the conductive layer, and the positive and negative electrodes between the sub-batteries are connected. Provide a transmission channel for the positive and negative electrodes of two adjacent sub-batteries.
[0153] Preferably, the laser frequency of the P2 scribing is 50-500 kHz, and the laser energy is 20-100 μJ.
[0154] Preferably, the width of the P2 scribing line is 40-300 μm, and the speed is 50-500 mm / s.
[0155] Typically but not limiting, the laser frequency of the P2 scribing line can be 50kHz, 100kHz, 200kHz, 300kHz, 400kHz or 500kHz, and the laser energy can be 20μJ, 40μJ, 60μJ, 80μJ or 100μJ, or any value in the range of 50kHz to 500kHz and 20μJ to 100μJ. The width of the P2 scribing line can be 40μm, 100μm, 160μm, 220μm or 300μm, and the speed can be 50mm / s, 100mm / s, 200mm / s, 300mm / s, 400mm / s or 500mm / s.
[0156] Preferably, the electrode material is deposited by vacuum evaporation to obtain the metal electrode. The metal electrode is deposited by vacuum thermal evaporation. The electrode material to be deposited can be a suitable conductive material such as copper, silver and gold. The vacuum degree of the equipment can be 10 -4 Pa to 5×10 -4 Within the Pa range, the deposition rate can be selected from 0.02-0.1 nm / s, and the deposition thickness can be selected from 50-200 nm. The deposition technology can also be selected from other suitable methods such as printing.
[0157] Preferably, the thickness of the metal electrode is 50-200 nm. Typically but not limiting, the thickness of the metal electrode may be 50 nm, 75 nm, 100 nm, 125 nm, 150 nm, 175 nm or 200 nm, or any value within the range of 50 nm to 200 nm.
[0158] Preferably, the electrode material includes copper, silver or gold.
[0159] The P3 line is scribed by a picosecond laser to separate the sub-cells. The frequency of the laser line can be selected in the range of 50 to 500 kHz, the energy can be selected in the range of 20 to 100 μJ, the width can be selected in the range of 40 to 300 μm, and the speed can be selected in the range of 50 to 500 mm / s.
[0160] P3 scribing is performed after the metal electrode layer is prepared. Its purpose is to separate the sub-batteries to form separate modules that block current conduction, so as to achieve the effect of increasing voltage and connecting batteries in series.
[0161] P4 scribing, also known as laser edge cleaning, is a process for cleaning the edge of the cell. The purpose is to remove the film layer of about 10mm width near the edge of the glass to form an insulating area as the back-end packaging area. This step helps to ensure the insulation of the edge of the cell, prevent short circuits and leakage, and also helps to improve the overall packaging quality of the cell.
[0162] The P4 scribing frequency can be appropriately selected within the range of 10 to 100 kHz, the energy can be appropriately selected within the range of 10 to 50 μJ, and the speed can be appropriately selected within the range of 100 to 1000 mm / s.
[0163] The present invention is further described below by specific examples and comparative examples, but it should be understood that these examples are only used for more detailed description and should not be understood as limiting the present invention in any form. The raw materials used in the examples and comparative examples of the present invention, if no specific conditions are specified, are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.
[0164] Example 1
[0165] This embodiment provides a perovskite solar cell, comprising the following steps:
[0166] 1. The transparent conductive glass adopts ITO substrate, and the size is 5×5cm. 2 , the frequency of P1 laser scribing is 200kHz, the energy is 50μJ, and the width is 100μm.
[0167] 2. Ultrasonic cleaning of ITO substrate, the cleaning agents are conductive glass cleaning liquid, deionized water, isopropyl alcohol. The conductive glass substrate should be completely immersed in the liquid, and each cleaning agent should be cleaned for 20 minutes. Take out the cleaned conductive glass substrate and dry it in a drying oven. The drying temperature is set to 70℃ and the time is 24 hours.
[0168] 3. Take out the dried ITO substrate and transfer it to the UVO ozone analyzer to clean and activate the glass surface for 15 minutes.
[0169] 4. Prepare the hole transport layer solution, dissolve 30 mg of [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (i.e. Me-4PACz) in 30 mL of ethanol solvent, shake thoroughly for 10 hours and filter. Prepare the hole transport layer by slit coating, and coat the hole transport layer in an air atmosphere with a relative humidity of 25%. First, clean the liquid inlet pipe of the slit coater with a blank solvent, and then apply 20 mL of the prepared hole transport layer solution. Place the ITO substrate to be coated in the slit coater, adsorb and fix it on the base, remove the surface dust with air blowing, set the length, width and thickness of the substrate, use 10 μL of hole transport layer solution per piece, the distance between the die and the substrate is 100 μm, the platform forward speed is 10 mm / s, start coating, and the die moves relatively from one end of the substrate to the other end at a uniform linear speed, coating a uniformly wet film on the substrate. The substrate coated with the hole transport layer was transferred to a hot stage and annealed at 100 °C for 10 min.
[0170] 5. Configure Cs 0.05 MA 0.1 FA 0.85 PbI3 perovskite precursor solution, 5.071g of lead iodide, 0.285g of methylamine hydroiodide, 1.832g of formamidine hydroiodide and 0.143g of cesium iodide are mixed and dissolved in 10mL of DMF and NMP mixed solvent to prepare a perovskite precursor solution, which is fully shaken for 10 hours and then filtered. The perovskite layer is prepared by slit coating. The perovskite layer is coated in an air atmosphere with a relative humidity of 20%. The plunger pump, die head and liquid inlet pipeline are first cleaned with DMF solvent, and then the conductive glass substrate to be coated is placed on the slit coater, and the dust on the glass surface is removed by air blowing. It is adsorbed and fixed on the coating base, and the length, width and thickness of the substrate are set. The amount of perovskite precursor solution per piece can be 20μL, the distance between the die head and the substrate is 100μm, and the platform forward speed is 10mm / s. Start coating, the die head moves from one end of the substrate to the other end at a constant speed, and a uniform wet film is coated on the substrate. The substrate coated with the perovskite precursor solution is transferred to a hot stage, first annealed on a 70°C hot stage for 1 minute, and then quickly transferred to a 120°C hot stage for annealing for 10 minutes to obtain a uniformly crystalline perovskite layer.
[0171] 6. Use continuous gas phase passivation method to modify the interface of perovskite layer. First place the isopropanol solution (concentration of 50 mg / mL) of short-chain ethylenediamine hydroiodide (EDADI) in a sealed container, heat it at 80°C to volatilize it, and fully passivate the surface interface defects of perovskite for 5 minutes. In the second step, place the isopropanol solution (concentration of 50 mg / mL) of 4-trifluoromethylphenylethylamine iodine (4-CF3-PEAI) as a passivator in a sealed container, heat it at 80°C to volatilize it, and the passivation time is 5 minutes.
[0172] 7. The electron transport layer material is C 60 , using vacuum thermal evaporation method, the vacuum degree of the equipment is 2×10 -4 Pa, the deposition rate is 0.01nm / s, and the deposition thickness is 30nm.
[0173] 8. The hole blocking layer material is BCP, and the vacuum thermal evaporation method is adopted, the evaporation temperature is 230°C, the deposition rate is 0.002nm / s, and the deposition thickness is 6.5nm.
[0174] 9. Use picosecond laser for P2 scribing, the frequency of laser scribing is 200kHz, the energy is 48.5μJ, the width is 50μm, and the speed is 200mm / s.
[0175] 10. Silver is deposited by vacuum thermal evaporation method, and the vacuum degree of electrode equipment is 2×10 -4 Pa. The deposition rate was 0.05 nm / s, the deposition thickness was 100 nm, and a silver electrode was obtained.
[0176] 11. P3 scribing was performed using a picosecond laser with a scribing frequency of 200kHz, an energy of 48.5μJ, a width of 50μm, and a speed of 200mm / s.
[0177] 12. Use P4 scribing to clean the edges and remove the residual impurities of P2 and P3 scribing to avoid short circuits. The frequency of laser scribing is 100kHz, the energy is 20μJ, the width is 100μm, and the speed is 500mm / s.
[0178] 13. Use encapsulation glue to encapsulate the components. On the bottom side, use UV resin to encapsulate the perovskite component through a 1mm thick glass substrate and anneal at 80℃ for 30s. Then use hot press bonding resin to encapsulate through a 1mm thick glass substrate on the top side and then anneal at 80℃ for 30s. Coat the edge of the module with UV resin encapsulation and irradiate with a 4W UV lamp for 30s to obtain a perovskite solar cell.
[0179] Example 2
[0180] This embodiment provides a perovskite solar cell, which is different from Embodiment 1 in that:
[0181] 4. Transfer the ITO substrate to the magnetron sputtering system to deposit the nickel oxide film. The pressure of the system is 5×10 -4 Pa. A small flow of oxygen was introduced during the sputtering process to improve the composition of the nickel oxide film. The substrate was heated moderately during the whole process. The thickness of the nickel oxide was monitored by a crystal oscillator and a film thickness meter. The deposition thickness was about 40nm. The substrate coated with the hole transport layer was transferred to a hot stage and annealed at 100℃ for 10min.
[0182] The remaining steps are the same as those in Example 1 and will not be described again.
[0183] Example 3
[0184] This embodiment provides a perovskite solar cell, which is different from Embodiment 1 in that:
[0185] 6. Use continuous gas phase passivation method to modify the interface of perovskite layer. First place isopropanol solution of propylenediamine iodine (concentration of 50 mg / mL) in a sealed container, heat it at 80°C to volatilize it, and fully passivate the surface interface defects of perovskite for 5 minutes. In the second step, place isopropanol solution of bis(trifluoromethylphenylethylamine) iodine (concentration of 50 mg / mL) as a passivator in a sealed container, heat it at 80°C to volatilize it, and the passivation time is 5 minutes.
[0186] The remaining steps are the same as those in Example 1 and will not be described again.
[0187] Example 4
[0188] This embodiment provides a perovskite solar cell, which is different from Embodiment 1 in that:
[0189] 6. Use continuous gas phase passivation method to modify the interface of perovskite layer. First place piperazine diiodide isopropanol solution (concentration is 50mg / mL) in a sealed container, heat it at 80℃ to volatilize it, and fully passivate the surface interface defects of perovskite for 5min. The second step is to place dodecyl ammonium iodide isopropanol solution (concentration is 50mg / mL) as a passivator in a sealed container, heat it at 80℃ to volatilize it, and the passivation time is 5min.
[0190] The remaining steps are the same as those in Example 1 and will not be described again.
[0191] Example 5
[0192] This embodiment provides a perovskite solar cell, which is different from Embodiment 1 in that:
[0193] 6. Use continuous gas phase passivation method to modify the interface of perovskite layer. First place methylammonium iodide isopropanol solution (concentration is 50mg / mL) in a sealed container, heat it at 80℃ to volatilize it, and fully passivate the surface and interface defects of perovskite for 5min. The second step is to place octylammonium iodide isopropanol solution (concentration is 50mg / mL) as a passivator in a sealed container, heat it at 80℃ to volatilize it, and the passivation time is 5min.
[0194] The remaining steps are the same as those in Example 1 and will not be described again.
[0195] Example 6
[0196] This embodiment provides a perovskite solar cell, which is different from Embodiment 1 in that:
[0197] 6. Use continuous gas phase passivation method to modify the interface of perovskite layer. First place isopropanol solution of diaminodiamine iodide (concentration of 50 mg / mL) in a sealed container, heat it at 80°C to volatilize it, and fully passivate the surface interface defects of perovskite for 5 minutes. The second step is to place isopropanol solution of p-fluorophenylethylamine iodine (concentration of 50 mg / mL) as a passivator in a sealed container, heat it at 80°C to volatilize it, and the passivation time is 5 minutes.
[0198] The remaining steps are the same as those in Example 1 and will not be described again.
[0199] Example 7
[0200] This embodiment provides a perovskite solar cell, which is different from Embodiment 1 in that:
[0201] The interface of the perovskite layer is modified by continuous gas phase passivation. An isopropanol solution (concentration of 1 mg / mL) of short-chain ethylenediamine hydroiodide (EDADI) is first placed in a closed container, heated at 80°C to volatilize it, and fully passivate the surface interface defects of the perovskite for 5 minutes. In the second step, an isopropanol solution (concentration of 1 mg / mL) of 4-trifluoromethylphenylethylamine iodine (4-CF3-PEAI) is first placed in a closed container as a passivator, heated at 80°C to volatilize it, and the passivation time is 5 minutes. The remaining steps are the same as in Example 1 and are not repeated here.
[0202] Example 8
[0203] This embodiment provides a perovskite solar cell, which is different from Embodiment 1 in that:
[0204] The perovskite layer is subjected to interface modification by continuous gas phase passivation. An isopropanol solution (concentration of 100 mg / mL) of short-chain ethylenediamine hydroiodide (EDADI) is first placed in a closed container, heated at 80°C to volatilize it, and fully passivate the perovskite surface interface defects for 5 min. In the second step, an isopropanol solution (concentration of 100 mg / mL) of 4-trifluoromethylphenylethylamine iodine (4-CF3-PEAI) is first placed in a closed container as a passivating agent, heated at 80°C to volatilize it, and the passivation time is 5 min. The remaining steps are the same as in Example 1 and will not be repeated here.
[0205] Example 9
[0206] This embodiment provides a perovskite solar cell, which is different from Embodiment 1 in that:
[0207] The perovskite layer is subjected to interface modification by continuous gas phase passivation. An isopropanol solution (concentration of 50 mg / mL) of short-chain ethylenediamine hydroiodide (EDADI) is first placed in a closed container, heated at 40°C to volatilize it, and fully passivate the surface interface defects of the perovskite for 8 minutes. In the second step, an isopropanol solution (concentration of 50 mg / mL) of 4-trifluoromethylphenylethylamine iodine (4-CF3-PEAI) is first placed in a closed container as a passivating agent, heated at 40°C to volatilize it, and the passivation time is 8 minutes. The remaining steps are the same as in Example 1 and are not repeated here.
[0208] Example 10
[0209] This embodiment provides a perovskite solar cell, which is different from Embodiment 1 in that:
[0210] The interface of the perovskite layer is modified by continuous gas phase passivation. An isopropanol solution (concentration of 50 mg / mL) of short-chain ethylenediamine hydroiodide (EDADI) is first placed in a closed container, heated at 80°C to volatilize it, and fully passivate the surface interface defects of the perovskite for 3 minutes. In the second step, an isopropanol solution (concentration of 50 mg / mL) of 4-trifluoromethylphenylethylamine iodine (4-CF3-PEAI) is first placed in a closed container as a passivator, heated at 80°C to volatilize it, and the passivation time is 3 minutes. The remaining steps are the same as in Example 1 and will not be repeated here.
[0211] Comparative Example 1
[0212] This comparative example provides a perovskite solar cell, which is different from Example 1 in that:
[0213] 6. Use a one-step gas phase passivation method to modify the interface of the perovskite layer. First, place an isopropanol solution of ethylenediamine hydroiodide (EDADI) in a sealed container and heat it at 80°C to volatilize it, fully passivating the surface and interface defects of the perovskite for 10 minutes.
[0214] The remaining steps are the same as those in Example 1 and will not be described again.
[0215] Comparative Example 2
[0216] This comparative example provides a perovskite solar cell, which is different from Example 1 in that:
[0217] 6. The interface of the perovskite layer is modified by a one-step gas phase passivation method. An isopropanol solution of 4-trifluoromethylphenylethylamine iodine (4-CF3-PEAI) is placed in a sealed container as a passivating agent, heated at 80°C to volatilize it, and fully passivate the interface defects of the perovskite surface for 10 minutes.
[0218] The remaining steps are the same as those in Example 1 and will not be described again.
[0219] Test Example 1
[0220] The semi-finished solar cells of Example 1 and Comparative Example 1 after step 6 were subjected to fluorescence spectroscopy. The obtained spectral graphs are as follows: Figure 2 shown.
[0221] Figure 2 As shown in the fluorescence spectrum, the higher the fluorescence intensity, the lower the surface defect state density of the perovskite film. Reducing the surface defect state density helps to suppress the non-radiative recombination of the surface interface, thereby improving the efficiency of large-area components. Therefore, it can be found that the defect state density of the perovskite film in Example 1 is significantly lower than that in Comparative Example 1, and continuous gas phase passivation can improve the efficiency of large-area components.
[0222] Test Example 2
[0223] The solar cells obtained in Example 1 and Comparative Example 1 were subjected to IV curves. Figure 3 shown.
[0224] from Figure 3 It can be seen that the component of Example 1 has a higher open circuit voltage, a higher current density and a fill factor. This is attributed to the fact that the continuous gas phase passivation can fully passivate the surface interface defects while promoting the arrangement of energy levels, thereby greatly improving the device performance of large-area perovskite components.
[0225] Test Example 3
[0226] The perovskite solar cells provided in the embodiments and comparative examples are subjected to performance tests to obtain the open circuit voltage V of the corresponding solar cells. oc , short circuit current density J sc , fill factor FF, photoelectric conversion efficiency PCE, the test results are shown in Table 1.
[0227] Table 1
[0228] <![CDATA[V oc (V)]]> <![CDATA[J sc (mA / cm 2 )]]> FF(%) PCE(%) Example 1 10.82 2.27 74.02 18.17 Example 2 10.84 2.23 73.20 17.69 Example 3 10.83 2.21 72.28 17.30 Example 4 10.79 2.24 74.45 18.00 Example 5 10.94 2.26 73.31 18.12 Example 6 10.85 2.22 72.20 17.39 Example 7 10.87 2.20 73.80 17.65 Example 8 10.89 2.21 71.79 17.28 Example 9 10.88 2.23 75.76 18.38 Example 10 10.91 2.25 74.79 18.36 Comparative Example 1 10.73 1.95 67.53 14.12 Comparative Example 2 10.64 2.01 68.95 14.75
[0229] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A passivation process for a perovskite layer, characterized in that: Performing a first passivation on the perovskite layer of the conductive substrate using a first passivator solution, and then performing a second passivation using a second passivator solution to obtain a passivation layer; Wherein, the number of C atoms of the first passivating agent is less than 5; The number of C atoms in the second passivator is ≥5.
2. The passivation process according to claim 1, characterized in that: The passivator is a first passivator and / or a second passivator; Preferably, the passivator includes at least one of a quaternary ammonium salt passivator, a phosphoric acid passivator, an organic amine passivator, a carboxylic acid passivator and a sulfonic acid passivator; Preferably, the concentration of the passivating agent solution is 1 to 100 g / L, preferably 40 to 60 g / L; Preferably, the conductive substrate containing the perovskite layer is inverted on the passivation solution so that the perovskite layer faces the passivation solution, and the passivation solution is heated or evacuated to volatilize the passivation agent and passivate to form a passivation layer; Preferably, the heating temperature is 40-80°C and the heating time is 3-8 minutes; Preferably, the vacuum degree of the vacuum extraction is 1-1000 Pa.
3. A process for preparing a perovskite solar cell, characterized in that: The invention comprises the passivation process as claimed in claim 1 or 2.
4. The preparation process according to claim 3, characterized in that: A hole transport layer, a perovskite layer, a passivation layer, an electron transport layer, a hole blocking layer and a deposited metal electrode are prepared in sequence on the pretreated conductive substrate to obtain the perovskite solar cell.
5. The preparation process according to claim 4, characterized in that: The pretreatment process includes P1 scribing, cleaning, drying and activation of the conductive substrate; Preferably, the conductive substrate comprises ITO glass or FTO glass, preferably ITO glass; Preferably, the laser frequency of the P1 scribing is 50-500kHz, and the laser energy is 20-100μJ; Preferably, the width of the P1 scribing line is 80-300 μm, and the speed is 100-300 mm / s; Preferably, the cleaning reagents include a cleaning solution for conductive glass, deionized water and an organic solvent used in this order; Preferably, the organic solvent comprises isopropyl ketone and / or acetone; Preferably, the cleaning time of each cleaning reagent is 15 to 25 minutes; Preferably, the drying method includes drying by oven drying or air gun drying; Preferably, the drying temperature is 60-80°C and the drying time is 18-36h; Preferably, the activation method includes ultraviolet ozone machine activation or plasma cleaning machine cleaning activation; Preferably, the activation time is 5 to 20 minutes.
6. The preparation process according to claim 4, characterized in that: The preparation method of the hole transport layer is as follows: The hole transport layer solution is coated on the pretreated conductive substrate by slit coating, spin coating, magnetron sputtering, doctor blading, inkjet printing or atomic layer deposition, and then annealed to obtain the hole transport layer; Preferably, the hole transport layer is made of Me-4PACz, PTAA, PETDOS:PSS, CuPc, poly-TPD, 2PACz, MeO-4PADBC or nickel oxide; Preferably, the solvent in the hole transport layer solution includes ethanol, 2-ME or DMF; Preferably, the annealing temperature is 80-120° C. and the annealing time is 8-12 min.
7. The preparation process according to claim 4, characterized in that: The preparation method of the perovskite layer is: The perovskite precursor solution is coated on the hole transport layer by slit coating, vacuum evaporation, magnetron sputtering, inkjet printing or doctor blade coating, and then high and low temperature annealing is performed to obtain a perovskite layer; Preferably, the high and low temperature annealing method is to first perform low temperature annealing and then perform high temperature annealing; Preferably, the low temperature annealing temperature is 60-80°C and the time is 30-90s; Preferably, the high temperature annealing temperature is 110-130°C and the time is 8-12 minutes; Preferably, the perovskite precursor solution includes at least one of methylamine hydroiodide, formamidine hydroiodide, rubidium iodide, lead iodide and lead bromide; Preferably, the solvent in the perovskite precursor solution includes at least one of DMF, NMP, 2-Me, DMSO and DMPU.
8. The preparation process according to claim 4, characterized in that: The preparation method of the electron transport layer is as follows: Depositing the electron transport layer material on the passivation layer by vacuum evaporation or magnetron sputtering to obtain the electron transport layer; Preferably, the thickness of the electron transport layer is 20 to 60 nm; Preferably, the electron transport layer material includes C60, PCBM or titanium dioxide.
9. The preparation process according to claim 4, characterized in that: The preparation method of the hole blocking layer is as follows: Depositing the hole blocking layer material on the electron transport layer by vacuum evaporation or atomic layer deposition to obtain the hole blocking layer; Preferably, the thickness of the hole blocking layer is 6 to 7 nm; Preferably, the hole blocking layer material includes BCP or tin dioxide.
10. The preparation process according to claim 4, characterized in that: Also included is P2 scribing after preparing the hole blocking layer and before depositing the metal electrode; Preferably, the laser frequency of the P2 scribing is 50-500kHz, and the laser energy is 20-100μJ; Preferably, the width of the P2 scribing line is 40-300 μm, and the speed is 50-500 mm / s; Preferably, the electrode material is deposited by vacuum evaporation to obtain a metal electrode; Preferably, the thickness of the metal electrode is 50 to 200 nm; Preferably, the electrode material includes copper, silver or gold.